THE ARCHITECTURE OF MEDICINE IN MOROCCO: BRIDGING THEORY AND PRACTICE - Borysenko, A.S.; A. Rhouzladi, A.; Morabih, M.; Kamar, B. (Municipal economy of cities. Series: «Economy science», 2025)
This study explores the architectural evolution of medical education and healthcare facilities in Morocco, focusing on integrating theoretical learning with practical training. It highlights design strategies such as flexible learning spaces and integrated medical-hospital models to enhance education, healthcare efficiency, and accessibility, creating a more effective and equitable system.